1, 25-dihydroxyvitamin D(3,) a potential role player in the development of thyroid disorders in schizophrenics - Malik, Arif (Pak J Med Sci, 2016)
OBJECTIVE: The present study was designed to assess the role of vitamin-D, in the development of autoimmune thyroid dysfunction in newly diagnosed schizophrenics. METHODS: For the present study 100 patients and 100 controls were screened out and studied for their thyroid antibodies, GSH, homocysteine, NOS and vitamin D levels by appropriate protocols to assess the underlying mechanism involved in the schizophrenics susceptible to autoimmune thyroid diseases. RESULTS: The results of the present study depicted that in schizophrenics, levels of cytokines like IL-6 (7.98±0.67 pg/ml), TNF-α, (40.76±6.98 pg/ml), homocysteine (16.98±1.09 µmol/L), Tg-Ab (30.93±3.87 IU/L), TPO-Ab (10.33±1.78 IU/L) and TSHr-Ab (3.76±0.055 IU/L) increased whereas, those of Vit-D (12.76±0.99 pmol/L), NOS (5.99±0.87 IU/L), GSH (4.48±.965 µg/dl) and NO (16.87±3.98 ng/ml) were decreased in the patients as compared to healthy control subjects. CONCLUSION: Vitamin-D in schizophrenia is involved in augmentation of hyperhomocysteinemia, inflammation, oxidative stress and thyroid antibodies, thereby playing a significant role not only in induction of schizophrenic symptoms but may also result in autoimmune thyroid diseases. Thus, earlier detection and rectification of its levels are helpful to limit the miseries of schizophrenia.